Model Based Investigation of Lithium Deposition Including an Optimization of Fast Charging Lithium Ion Cells. Issue 5 (20th May 2021) - Hovestadt, L.; Lux, S.; Koellner, N.; Schloesser, A.; Hanke-Rauschenbach, R.
Abstract : Simulating the properties of lithium ion cells during charging becomes more and more important to understand the ongoing effects during fast charging. In this work special emphasis is given to the modelling of metallic lithium deposition on the surface of negative electrode particles, so-called lithium plating, and the linked mechanical behaviour. The basis of the parametrization of the electrochemical model was a previously published experimental study on the pressure behaviour under lithium plating conditions. The developed and parametrized simple pseudo two-dimensional model reproduces the experimental study on lithium plating with a satisfying accuracy of simulated voltage and pressure trend. The model enables prediction of lithium deposition onset by matching measured pressure behaviour to the model. In addition to reproducing the cell behaviour, the model was used to optimize a measurement based fast charging protocol by using the negative electrode potential. The optimization of the fast charging protocol resulted in a 6.3% decreased charging time from 0 to 85%SoC while using a maximum C-rate of 3C. A verification of the model-based optimization has been shown by short experimental study.